Réponses

Meilleure réponse !
2013-11-10T14:24:44+01:00
Bonjour

A = (x+4)(x-6) + (-1+x)(x-7)
A = x² -6x +4x -24 + (-x +7 +x² -7x)
A = x² -6 +4x -24 -x +7 +x² -7x
A = 2x² -4x +1

B = (x-1)(5x -2) - (-6 +3x)(-1+x)
B = 5x² -2x -5x +2 - (6 -6x -3x +3x²)
B = 5x² -2x -5x +2 -6 +6x +3x -3x²
B = 2x² +2x -4

C = - (3x-8)(x+4) - (7x -8)(-1+7x)
c = - (3x² +12x -8x -32) - (-7x +49x² +8 - 56x)
C = -3x² -12x +8x +32 +7x -49x² -8 +56x
C = -52x² +59x + 24

D = - (6x -8x² -15 + 20x) + ( -12x² -6x +18x +9)
D = -6x +8x² +15 -20x -12x² -6x +18x +9
D = -4x² -14x +24